Circulating adiponectin concentrations in patients with congestive heart failure. Issue 10 (18th April 2006) - George, J; Patal, S; Wexler, D; Sharabi, Y; Peleg, E; Kamari, Y; Grossman, E; Sheps, D; Keren, G; Roth, A
Abstract : Objectives: To determine concentrations of adiponectin and its predictive value on outcome in a cohort of patients with congestive heart failure (CHF). Methods: Serum and clinical data were obtained for outpatients with clinically controlled CHF (n  =  175). Serum concentrations of adiponectin, C reactive protein, N-terminal pro-brain natriuretic peptide (NT-proBNP), interleukin (IL) -1β, IL-6, IL-8, IL-10, IL-12, tumour necrosis factor α and CD-40 ligand were determined. The association of adiponectin with the clinical severity of CHF was sought as well as the predictive value of this adipokine on mortality, CHF hospitalisations or the occurrence of each of these end points. Results: Concentrations of adiponectin were significantly increased in patients with CHF. Patients with higher New York Heart Association class had significantly higher serum concentrations of adiponectin. Adiponectin serum concentrations were lower in patients with diabetes and CHF as well as in patients with ischaemic cardiomyopathy. Serum adiponectin concentration was positively associated with age and NT-proBNP but was negatively correlated with C reactive protein concentrations. Serum adiponectin above the 75th centile was found to be an independent predictor of total mortality, CHF hospitalisations or a composite of these end points over a two-year prospective follow up. Conclusion: Adiponectin is increased in CHF patients and predicts mortality and morbidity.